Performance of a non-contact veterinary infrared thermometer and reference intervals of equine temperature at different body sites - Alberghina, Daniela; Tombolani, Carlotta; Quintavalla, Fausto (Frontiers in Veterinary Science, 2025)
Evaluating the body temperature of horses (Equus caballus) is essential for monitoring their health. Rectal thermometry is the most common method for determining the temperatures of adult horses and foals. However, this method requires restraining the animals for several seconds, and it poses potential risks to both horses and humans. This study compared infrared and rectal thermometry in 126 horses, evaluating age and measurement site influences on body temperature. Horses were divided into three groups: foals (4–12 months), Shetland ponies (8–12 months), and adult horses (2–30 years). Rectal, ocular, gingival, and perineal temperatures were recorded to assess the potential of non-invasive infrared methods. Reference intervals of temperature at different body sites are provided. No significant differences were found in gingival and perineal temperatures among groups. Foals showed significantly higher rectal temperatures than adults (p < 0.001), likely due to age. Shetland ponies showed higher ocular temperatures than foals and adult horses (p < 0.05, p < 0.001), probably because they were influenced by ambient temperature, which significantly correlated with ocular readings. Significant positive correlations existed between ocular and rectal (p < 0.01) and perineal and rectal temperatures (p < 0.0001). Bias was −0.2°C (ocular vs. rectal) and 2°C (perineal vs. rectal). Perineal temperature, despite numerical differences, correlated well with rectal temperature, allowing indirect estimation with a correction factor, and was unaffected by ambient temperature. This suggests infrared perineal temperature may be a viable rectal thermometry alternative for estimating equine body temperature, enhancing animal welfare through non-invasive methods.